The Influence of Third Party Funds and Inflation on Profitability with Profit Sharing Financing as a Mediating Variable - Kurniawan, Agus; sabilla, Shifa; Amrina, Dania Hellin (Universitas Islam Negeri Raden Intan, 2024)
This study aims to determine and analyze the effect of DPK and inflation on the profitability (ROA) of Bank Muamalat Indonesia with profit sharing financing as a mediating variable. The population in this study is the entire annual financial report at PT. Bank Muamalat Indonesia which has been published since the first quarter of 2018 to the fourth quarter of 2022, which is 20 populations. The data analysis techniques used are descriptive statistical tests, classical assumption tests and path analysis. Data processing in this study uses the IBM SPSS Statistic 26 tool. Based on the results of the path analysis test, it shows that the DPK variable has a positive and significant effect on the profitability of Bank Muamalat Indonesia. The inflation variable has a negative and significant effect on the profitability of Bank Muamalat Indonesia. The DPK variable has a positive and significant effect on profit sharing financing. The Inflation variable does not affect profit sharing financing. Profit sharing financing has a positive and insignificant effect on profitability. Profit sharing financing cannot mediate the effect between third party funds on profitability. Profit sharing financing can mediate the effect between third party funds on profitability.